Methods for regionalization of impacts of non-toxic air pollutants in life-cycle assessments often tell a consistent story. (November 2017) - Djomo, S. Njakou; Knudsen, M.T.; Andersen, M.S.; Hermansen, J.E.
Abstract: There is an ongoing debate regarding the influence of the source location of pollution on the fate of pollutants and their subsequent impacts. Several methods have been developed to derive site-dependent characterization factors (CFs) for use in life-cycle assessment (LCA). Consistent, precise, and accurate estimates of CFs are crucial for establishing long-term, sustainable air pollution abatement policies. We reviewed currently available studies on the regionalization of non-toxic air pollutants in LCA. We also extracted and converted data into indices for analysis. We showed that CFs can distinguish between emissions occurring in different locations, and that the different methods used to derive CFs map locations consistently from very sensitive to less sensitive. Seasonal variations are less important for the computation of CFs for acidification and eutrophication, but they are relevant for the calculation of CFs for tropospheric ozone formation. Large intra-country differences in estimated CFs suggest that an abatement policy relying on quantitative estimates based upon a single method may have undesirable outcomes. Within country differences in estimates of CFs for acidification and eutrophication are the results of the models used, category definitions, soil sensitivity factors, background emission concentration, critical loads database, and input data. Striking features in these studies were the lack of CFs for countries outside Europe, the USA, Japan, and Canada, the lack of quantification of uncertainties. Parameter and input data uncertainties are well quantified, but the uncertainty associated with the choice of category indicator is rarely quantified and this can be significant. Although CFs are scientifically robust, further refinements are needed before they can be integrated in LCA. Future research should include uncertainty analyses, and should develop a consensus model for CFs. CFs for countries outside Europe, Japan, Canada and the USA are urgently needed. Highlights: A summary of CFs for acidification, eutrophication and tropospheric ozone is made. Comparison of CFs is performed and uncertainties in CFs are identified and classified. Estimates of CFs vary substantially across studies. Uncertainties related to modeler's choice are not quantified and can be significant. CFs for regions outside Europe and USA is needed as well as a consensus model for CFs.